(untitled) (Fourth World Journal, 2026)
This article shares the traditional knowledge of Kichwa midwife Conzuelo (“Mamá Conzuelo”) Tapullima de Tuanama Tuanama about pregnancy, childbirth, and the use of medicinal plants in the community of Chirik Sacha, San Martín, Peru. Through interviews and visits to her garden, the text highlights four essential plants and the teachings that accompany them. Laura Corradi wrote the premises, acknowledgments, introduction, and conclusions, situating Mamá Conzuelo’s knowledge within the broader context of the stigmatization of Indigenous midwifery and the cultural revitalization efforts taking place in the region. The article aims to support the preservation of this knowledge and underscores its importance for community health and for recognizing the central role of midwives within an intercultural framework.